Towards a Methodological Basis the Study of the «Fourth Power» as an Institution of the Political System within Modern Society - V. P. Miletskiy; Ya. A. Emelin (Дискурс)
Introduction. This article considers the mass media as the «Fourth Power» in the political system of modern society with the aim of illuminating the place of mass media in the latter. The authors had attempted to achieve this goal in terms of structural-functional, institutional and other explanatory concepts. From a theoretical point of view, the media attract the attention of both political scientists and sociologists, philosophers, historians, journalists and public relations specialists. Research in this direction requires a multiparadigmal methodological approach, since all theoretical and empirical resources for such analysis are available in modern science. Methodology and sources. In the framework of these methodological positions (multiparadigmal methodological approach) “The Fourth Power” appears in various aspects, which also allows to study the latter as an institution of the political system of society, in which the media are not only an indicator of the development of civil society, but also indicate the degree of openness of the political elite and the ruling political class. As methodological sources, this article uses the works of such founders of the concept of “Fourth Power” as J. S. Mill, J. Bentam, J. Habermas, F. Siebert, T. Peterson, W. Schram, etc. Results and discussion. The article studies the possibilities of applying the basic provisions of general scientific and specialized approaches to the study of the concept of «Fourth Branch of Power» as an explanatory methodological approach in modern political and sociological researches. The authors made an attempt to theoretical interpretation of the basic categories and to highlight their conceptual analogues in modern science.Conclusion. The results of the work show that the mass media (“The Fourth Power”) definitely play an ever-increasing role in terms of control over public power and are one of the institutions of civil-political society. Although it is known that the use of the term “The Fourth Power” to denote this political role of the media may cause objections and be a reason for discussion.